2015
DOI: 10.1007/s11224-015-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy of formation of guanidine and its amino and nitro derivatives

Abstract: The gas-phase enthalpies of formation (D f H 298 ) of guanidine and its 10 amino and nitro derivatives were calculated using the isodesmic reaction method at the Gaussian-4 level of theory. The enthalpies of sublimation (D sub H 298 ) were estimated in the framework of the Politzer approach that combines the empirical equation for enthalpy of sublimation with the B3LYP/cc-pVTZ calculations of the electronic properties of the molecular surfaces. The enthalpies of sublimation of mono-, di-, and triaminoguanidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…To calculate the gas-phase enthalpies of formation, we use the composite quantum chemical G4 method in combination with isodesmic reactions approach . In our recent publications, we have shown that the G4 method applied to atomization reaction could resulted in large errors for nitrogen containing compounds, whereas the use of isodesmic reactions allowed us to achieve an accuracy comparable with that obtained from the experimental measurements. The same picture is observed for other composite methods: the average of CBS-QB3, CBS-APNO, G3, and G4 methods obtained for hydrazine using isodesmic reactions (97.7 ± 2.0 kJ/mol) is in close agreement with results of high-level W4, CCSD­(T)-F12b, and W3X-L calculations (97.3, 97.4, and 97.5 kJ/mol, respectively), whereas the average value calculated using atomization reactions (100.8 ± 2.0 kJ/mol) is substantially higher.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…To calculate the gas-phase enthalpies of formation, we use the composite quantum chemical G4 method in combination with isodesmic reactions approach . In our recent publications, we have shown that the G4 method applied to atomization reaction could resulted in large errors for nitrogen containing compounds, whereas the use of isodesmic reactions allowed us to achieve an accuracy comparable with that obtained from the experimental measurements. The same picture is observed for other composite methods: the average of CBS-QB3, CBS-APNO, G3, and G4 methods obtained for hydrazine using isodesmic reactions (97.7 ± 2.0 kJ/mol) is in close agreement with results of high-level W4, CCSD­(T)-F12b, and W3X-L calculations (97.3, 97.4, and 97.5 kJ/mol, respectively), whereas the average value calculated using atomization reactions (100.8 ± 2.0 kJ/mol) is substantially higher.…”
Section: Introductionsupporting
confidence: 77%
“…Two thiocarbohydrazides (26,27) are presented in Table 2. Two experimental values of Δ f H 298 °(cr) for 26 differ by about 20 kJ/mol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• (s) of guanidinium nitrate (−386.9 kJ•mol −1 ) [37], guanidine (−56.1 kJ•mol −1 ) [37], and liquid nitric acid (−174.10 kJ•mol −1 ) [24] are available in the literature. The value for ∆ r H can then be obtained from Equations ( 10) and (11).…”
Section: Computational Results For Gztmentioning
confidence: 99%